Notes on the Political Economy of Green Transition: A conversation with Ioannis Kampourakis - Loxa, Alezini ; 0000-0002-7345-6266; Menon, Mahesh; Kampourakis, Ioannis (Nordic Journal of European Law, 2025)
This article presents a conversation with Dr. Ioannis Kampourakis, Associate Professor of Law and Markets at Erasmus University Rotterdam, as part of Lund University’s Screening for Sustainability project. Kampourakis’ research explores the political economy of the green transition, focusing on how markets can be deliberately designed and steered—what he calls ‘market instrumentalism’—to achieve sustainability goals. Drawing on Kampourakis’ research, Dr. Alezini Loxa and PhD candidate Mahesh Menon enter into a conversation about the political economy of green transition with a focus on the European Green Industrial Policy. They discuss with Kampourakis about the changing role of law in relation to state capitalism, the potential for democratic control over the green transition, the challenges that arise for countries in the Global South as well as the recent political backlash both in the EU and in the US to sustainability related policies.
Keywords: Environmental law; Miljörätt